PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA PEMBELAJARAN EDPUZZLE TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS XI SMA NEGERI 1 DUA KOTO - Listia Aisyah; Anggraini, Dewi; Mohamad Hafrison; Andria Catri Tamsin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by students' low poetry writing skills, particularly in the use of diction, figures of speech, imagery, and concrete words. This study aims to analyze the effect of the Project-Based Learning model assisted by Edpuzzle media on the poetry writing skills of eleventh-grade students at SMA Negeri 1 Dua Koto. This research was quantitative with a quasi-experimental design using a one-group pretest-posttest design. The study population was 182 students, while the sample was 32 students from class XI F7, selected using a purposive sampling technique. The research instrument was a poetry writing performance test assessed based on indicators of diction, figurative language (figures of speech), imagery, and concrete words. Data were analyzed using normality tests, homogeneity tests, and t-tests. The results showed that students' poetry writing skills before treatment were at the Nearly Adequate (HC) level with an average score of 57.03, while after treatment they improved to Good (B) with an average score of 83.28. Thus, there was an increase of 26.25%. The results of the hypothesis test show that t count > t table, so H₁ is accepted and H₀ is rejected. This proves that the Project Based Learning model assisted by Edpuzzle media has a significant effect on students' poetry writing skills.